Gaining insights in the nutritional metabolism of amphibians: analyzing body nutrient profiles of the African clawed frog, Xenopus laevis - Brenes-Soto,Andrea; Dierenfeld,Ellen S.; Bosch,Guido; Hendriks,Wouter H.; Janssens,Geert P.J. (PeerJ, 2019)
Whole bodies of Xenopus laevis (n = 19) were analysed for chemical composition and morphometrics. The nutrient profile (macronutrients, amino acids, fatty acids and minerals) was evaluated by sex; interactions among variables with body weights and lengths, and comparisons made with different species of marine and fresh water fish. Significant differences were found in morphometric measurements, water content, several minerals and fatty acids between sexes of X. laevis. Amino acid profiles differed in methionine, proline and cysteine, which could underlie different metabolic pathways in frogs when compared to fish. In addition, fatty acid profiles revealed more monounsaturated and n − 6 polyunsaturated fatty acids in frogs than in fish, more similar to values reported for terrestrial than aquatic vertebrates. Important interactions were also found between body measurements and fat, calcium, and phosphorus, as well as between essential and non-essential amino acids. The results indicate that frogs might have particular biochemical pathways for several nutrients, dependent on sex and linked to body weight, which ultimately could reflect specific nutrient needs.
Keywords: Metabolism; Nutrition; Xenopus laevis; Body composition; Amino acids; Fatty acids